PRAKTIK PEMBAGIAN WARIS BERDASARKAN HUKUM WARIS ISLAM: (Studi Kasus di Kelurahan Pekan Arba RT. 01/ RW. 01) - Herdiansyah; M. Ridwan; Al-amin, Muhammad Bagus; Widayanti, Dewi; Muda, Sultan Iskandar; Juari, Iskandar (Indra Institute Research & Publication, 2024)
This research aims to analyze the practice of distributing inheritance (inheritance) based on Islamic law in Muslim society. Pekan Arba Village RT. 01/ RW. 01 was used as the location for this research. Namely how the people of Pekan Arba Village, who are predominantly Muslim, apply Islamic inheritance law in the midst of their lives. The method used in this research is empirical sociological research by going directly to the community through interviews with several figures and the community in Pekan Arba RT. 01/ RW. 01. The data from the interviews were then analyzed and processed using the descriptive diductive method. This research can then be concluded that the practice of dividing inheritance based on Islamic inheritance law in the Pekan Araba Village RT 01/ RW 01 community is still relatively low. Therefore, there must be efforts from the sub-district government or local religious leaders so that the community has legal awareness that as a Muslim, carrying out inheritance distribution based on Islamic inheritance law is an obligation.